2017
DOI: 10.17223/19988613/49/3
|View full text |Cite
|
Sign up to set email alerts
|

The Clay "Rattle" in the Shape of Bear Head and the Variants of Its Usage by the Population of Krotovo Culture (Bronze Age, the end of the 3rd millennium BC, Baraba Forest-Steppe)

Abstract: Приводится всесторонний анализ глиняной погремушки в виде головы медведя, обнаруженной на поселении кротовской культуры Венгерово-2 (Барабинская лесостепь). Представлены результаты морфологического, рентгеноскопического и технологического исследования артефакта. Предложены основные варианты функциональной интерпретации изделия: детская игрушка, ритуальный предмет, музыкальный инструмент. Приведены археологические, этнографические и этноисторические параллели. Сделан вывод о многофункциональности изделия. Ключе… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similar to the ST bronzes, these daggers are also characterized by an advanced level of metalwork, and some have suggested that they are possibly related to the ST phenomenon (Molodin 1993; Parzinger 2000). These items, like the ST objects, mostly represent occasional findings from Central Asia (East Kazakhstan, Altai, and Xinjiang) and southwestern Siberia (Chlenova 1976; Aleshin and Vladimirov 1984; Molodin 1993, 2015; Samashev and Zumabekova 1993; Grushin et al 2006, 2009; Kiryushin et al 2006; Kovalev 2013). As to closed complexes, to date, only two are known to have contained daggers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the ST bronzes, these daggers are also characterized by an advanced level of metalwork, and some have suggested that they are possibly related to the ST phenomenon (Molodin 1993; Parzinger 2000). These items, like the ST objects, mostly represent occasional findings from Central Asia (East Kazakhstan, Altai, and Xinjiang) and southwestern Siberia (Chlenova 1976; Aleshin and Vladimirov 1984; Molodin 1993, 2015; Samashev and Zumabekova 1993; Grushin et al 2006, 2009; Kiryushin et al 2006; Kovalev 2013). As to closed complexes, to date, only two are known to have contained daggers.…”
Section: Introductionmentioning
confidence: 99%
“…Closed complexes containing daggers with figure handles: 9 – burial ground Sopka 2/4B; 12 – the Second Karakol Hoard. Map sources: Chernykh (2015), Chlenova (1976), Alekhin and Vladimirov (1984), Molodin (1983, 1993, 2013, 2015), Samashev and Zumabekova (1993), Grushin et al (2006), Kiryushin et al (2006), Molodin et al (2007, 2011), Kovalev (2013), and Kuzminykh (2011). Map adapted from Encarta Microsoft 2006.
Figure 2 Seima-Turbino objects ( 4, 5 – stone, other – bronze) from the burial grounds of southwestern Siberia.
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation